THE EXEMPLARY STATEMENT OF FAITH OF THE THREE YOUNG JEWS IN DANIEL 3:16-18: AN EXAMPLE FOR CHRISTIANS TODAY - Ngowi, William (Studia Theologica Varsaviensia, 2025)
Studying the Court Tale found in chapter 3 of the book of Daniel led to the proposition that its key message is based on response of Shadrach, Meshach and Abednego to king Nebuchadnezzar’s interrogation, “But even if he does not, we want you to know, O king, that we will not serve your gods or worship the image of gold you have set up” (3:18). The three young Jews did not put their trust in God based on whether He will rescue them on not. The point of the tale is not about whether God exists or more powerful than the gods of the Chaldeans. Rather, it is their exemplary statement of faith and trust which they demonstrated before king Nebuchadnezzar and his officers. This is in contrast with some exegetes who hold that the purpose was to compare the God of Israel and the Chaldean gods in order to demonstrate which god had absolute influence in the Babylonian kingdom. Such conclusion derives from the fact that the original command and decree of the king did not request the people to worship his gods; rather, the image he had raised up (3:5, 7, 10, 15). Indeed, the refusal to “serve your gods” was added by the Chaldeans in their accusation against the three young Jews (3:12b). Again, the chiastic structure of the narrative makes 3:18 the pivot of the story, in which the two antithetic royal decrees (3:4-6; cf. 10, 12 and 3:29) form an inclusion. Therefore, the key message of the story was to demonstrate the firm trust in God without relying on signs or empirical proofs. It is conventionally accepted by scholars that though the historical setting of the tale goes back to the period of the Babylonian Deportation (ca. 597-539 B.C.), it was written between the 3rd -2nd century B.C. purported to inspire pious Jews to persevere in their faith under the oppression and persecution of Seleucid’s king Antiochus IV Epiphanes, the Greek king of the Seleucid Empire of Judea in 167–164 BC. Similarly, the example of pure trust in God of Shadrach, Meshach and Abednego is extremely relevant for our contemporary times when the Church is facing formidable challenges from within and without of believers who have become itinerant seekers of spectacles of miracles of healing and wealth, known as the gospel of prosperity. Jesus himself was against such sign or miracle seekers, whom he called “An evil and adulterous generation seeks for a sign” (Mt 12:38-39; 16:4; cf. Lk 11:29-32).